2021
DOI: 10.1002/brb3.2251
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor attenuates cognitive impairment and motor deficits in a mouse model of Parkinson's disease

Abstract: Background: Parkinson's disease (PD) is one of the most common neurodegenerative disorders that seriously impair the life quality and survival of patients. Herein, we aim to investigate the neuroprotective roles of brain-derived neurotrophic factor (BDNF) in PD mice and reveal the underlying mechanisms. BDNF overexpression was achieved via the injection of adeno-associated viruses (AAV) with BDNF gene. Methods: PD mouse model was established by 1-methyl-4-phenyl-1,2,3,6tetrahydropyridine (MPTP) treatment. Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Some neurotrophic factors promote tissue repair and regeneration after nerve injury, which exerts anti-in ammatory, antiapoptotic and axon regeneration effects [40]. Moreover, BDNF alleviated mitochondrial dysfunction and enhanced the Complex I activity in MPTP mice [41]. Similarly, with the previous research [42,43], our study found that neurotrophic factors GDNF, BDNF and CDNF decreased signi cantly in both MPP + and MPTP models.…”
Section: Discussionsupporting
confidence: 85%
“…Some neurotrophic factors promote tissue repair and regeneration after nerve injury, which exerts anti-in ammatory, antiapoptotic and axon regeneration effects [40]. Moreover, BDNF alleviated mitochondrial dysfunction and enhanced the Complex I activity in MPTP mice [41]. Similarly, with the previous research [42,43], our study found that neurotrophic factors GDNF, BDNF and CDNF decreased signi cantly in both MPP + and MPTP models.…”
Section: Discussionsupporting
confidence: 85%
“…91 Injection of adeno-associated virus with the BDNF gene mitigates mitochondrial damage, cognitive disorders, and loss of dopaminergic neurons more effectively in PD mice. 92 Exercise can improve motor and cognitive impairments by regulating BDNF in PD patients. 93 Through intranasal delivery of BDNF to the target area of the brain, the immunoreactivity of tyrosine hydroxylase was significantly increased, concomitant with improved locomotory function in PD mice.…”
Section: The Bdnf/trkb Signaling Pathwaymentioning
confidence: 99%
“…BDNF supports the midbrain dopaminergic neurons surviving, promotes differentiation, and protects dopamine neurons from neurotoxins ( Minichiello et al, 2002 ). BDNF overexpression alleviated motor deficits and cognitive impairment in MPTP-induced PD mice through mitigating mitochondrial damage ( Chang and Wang, 2021 ). What’s more, BDNF level was significantly decreased in the colon of MPTP-treated group compared to the vehicle-treated group, indicating a role of BDNF in the gut-brain axis in PD ( Choi et al, 2021 ).…”
Section: Pathological Functions Of Brain Derived Neurotrophic Factormentioning
confidence: 99%